1997
DOI: 10.1038/42961
|View full text |Cite
|
Sign up to set email alerts
|

C-terminal binding domain of Rho GDP-dissociation inhibitor directs N-terminal inhibitory peptide to GTPases

Abstract: The Rho GDP-dissociation inhibitors (GDIs) negatively regulate Rho-family GTPases. The inhibitory activity of GDI derives both from an ability to bind the carboxy-terminal isoprene of Rho family members and extract them from membranes, and from inhibition of GTPase cycling between the GTP- and GDP-bound states. Here we demonstrate that these binding and inhibitory functions of rhoGDI can be attributed to two structurally distinct regions of the protein. A carboxy-terminal folded domain of relative molecular ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
148
2
1

Year Published

1998
1998
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(162 citation statements)
references
References 25 publications
11
148
2
1
Order By: Relevance
“…We observed that phosphorylation of RhoGDI by Src does not occur with preformed Rho GTPase-RhoGDI complexes, but requires RhoGDI to be in the uncomplexed state. This observation is consistent with the location of Tyr156 within an acidic region at the interface of the binding site on RhoGDI for Rho GTPases, as described in several structural analyses of GTPase-GDI complexes (Gosser et al, 1997;Keep et al, 1997;Hoffman et al, 2000). As a consequence of phosphorylation at Tyr156, we show that binding of RhoGDI to Rho GTPases (RhoA, Rac1, and Cdc42) is substantially reduced, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…We observed that phosphorylation of RhoGDI by Src does not occur with preformed Rho GTPase-RhoGDI complexes, but requires RhoGDI to be in the uncomplexed state. This observation is consistent with the location of Tyr156 within an acidic region at the interface of the binding site on RhoGDI for Rho GTPases, as described in several structural analyses of GTPase-GDI complexes (Gosser et al, 1997;Keep et al, 1997;Hoffman et al, 2000). As a consequence of phosphorylation at Tyr156, we show that binding of RhoGDI to Rho GTPases (RhoA, Rac1, and Cdc42) is substantially reduced, both in vitro and in vivo.…”
Section: Discussionsupporting
confidence: 91%
“…Complexation of Rho, Rac, or Cdc42 with GDIs inhibits GDP dissociation and localizes GTPases to the cytosol in inert forms unable to interact with GEFs (guanine nucleotide exchange factors), GAPs (GTPase activating proteins), or effector targets (Van Aelst and Souza-Schorey, 1997;DerMardirossian and Bokoch, 2005). GDIs maintain Rho GTPases as soluble cytosolic proteins by forming high-affinity complexes that mask the C-terminal geranylgeranyl membrane-targeting moiety within a hydrophobic pocket formed by the immunoglobulin-like domain of RhoGDI (Gosser et al, 1997;Keep et al, 1997;Hoffman et al, 2000). When Rho proteins are released from GDIs, they insert into the membrane lipid bilayer through their isoprenylated and polybasic C-terminal domains to be activated by membrane-associated GEFs, initiating the association with effector targets at the membrane.…”
Section: Introductionmentioning
confidence: 99%
“…The charge states of the carboxyl ends of the prenylated proteins may determine both their structures and the nature of the interactions with other proteins that are dependent on the polyisoprenyl moiety and vicinal groups. A polyisoprenyl-binding pocket was demonstrated on the Rho dissociation inhibitor [6] that strongly indicates the importance of the farnesyl or geranylgeranyl moiety and indeed of the prenylation pathway changes on protein-protein interactions. Furthermore, a strong influence on physiological well being was demonstrated with mice deficient in isoprenyl carboxylmethyl transferase (PPMTase) which, unable to methylate prenylated protein substrates, did not survive through midgestation [20].…”
Section: Discussionmentioning
confidence: 88%
“…This is perhaps more substantial based on the fact that the isoprenyl group of proteins such as the G-protein γ subunits are essential for their coupling of receptor-derived signals to such effector enzymes as the adenylyl cyclases and phospholipase Cβ2 [2,4,5]. Furthermore, an isoprenyl-binding site has been identified using solution NMR on Rho dissociation inhibitor [6]. Prenyl-Lcysteine (PC) analogs that mimic only the C-terminal prenylated cysteine residue of prenylated proteins exert physiological effects such as the inhibition of platelet aggregation [2] or SAM-induced Parkinson's disease-like effects in rats through mechanisms that do not involve the inhibition of the prenylated protein methyltransferase [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Geranylgeranyl modification is important for cellular trafficking and targets these Rho GTPases to the cellular membrane (10,26). The membrane translocation of inactive or GDP-bound Rho involves the release of its cytoplasmic inhibitor, Rho guanine nucleotide dissociation inhibitor, and activation of Rho through GDP/GTP exchange in the presence of guanine nucleotide exchange factor (27)(28)(29). Since most of the cytoplasmic Rho proteins are inactive (GDP-bound state), their GTP binding activity remains invariably low even in the presence of HMG-CoA reductase inhibitor treatment.…”
Section: Effects Of Rho On Smooth Muscle Cell Cycle Progression-tomentioning
confidence: 99%